ISU SEKSUALITAS DALAM KOMUNIKASI KELUARGA - Maria Margaretha Okky Triani (Jurnal Ilmu Komunikasi Acta Diurna, 2020)
This article explains about messages of sexualities from parents to their children with Javanese cultural background. This research use the guideline of sex education from UNESCO to explore the sex education practices in Semawung. The informants are three families in Semawung, The result shows that sexuality still considered as a taboo by families in Semawung. In the biological dimension, parents give messages in the form of commands and prohibitions. In the psychological dimension, families in Semawung Hamlet view gender and gender roles according to traditional and modern perspectives. In the social dimension, parents give messages about discrimination, human rights, sexual harassment, violence and bullying. In the cultural dimension, the family in Semawung Hamlet is a family that lives in Javanese culture. In addition, the family uses the language and symbols exchanged in conveying the message.